A CLINICAL EVALUATION OF THE EFFICACY OF AMRITSAAR LOHOKTA DOSHANIWARAK DRAVYAS IN THALASSAEMIA MAJOR PATIENTS WITH RESPECT TO ITS EFFECT ON IRON OVER-LOADING - Narode, Sagar; Choudhary, Neelam (International Journal of Ayurveda and Pharma Research, 2015)
Background: Thalassaemia Major a hereditary blood disease, widespread in the Mediterranean countries, Asia and Africa and mortality is primarily due to iron overload. Here, we present a clinical study to evaluate the efficacy of Amritsaar Lohokta Doshaniwarak Dravyas Thalassaemia Major Patients with respect to its effect on iron overload. Methods: In this study, Thalassaemia patients having age-group of 5 to 14 years were selected irrespective of their sex & religion. A total number of 40 patients were taken for the study and were randomly placed in Group A & Group B. The study was carried out for 21 days. The Group A patients were administered Deferiprone 20mg/kg body weight and Lohadosh Niwarka Yogin the dose of 3gm/day. Trial was conducted for twenty one days and follow-up was taken after every seventh day. Patients of this group were told to eat Petha two pieces (approx 50gms) every day as a Pathya. The group B patients were administered Deferiprone 20 mg/kg body weight. These patients were also told to follow the same dietary changes already advised by the Thalassaemia Day Care Centre. Result: Effect on Arochaka, Mandagni, Angamard, Fatigue, Joint Pain, Abdominal Pain, Dyspnoea, Pallor, IBS, Recurrent URTI, SGPT, Sr. Urea, Sr. Creatinine in Group A were statistically highly significant and Group B showed statistically non significant results. Effect on splenomegaly in Group A was statistically significant and in Group B was statistically non significant. Effect on Hepatomegaly in Group A and in Group B was statistically non significant. Conclusion: The Lohadosh Nivaraka yoga shows distinct activity. It significantly improves the general condition, helps to reduce splenomegaly and ferritin levels, boosts immunity and reduces debility. Hence it can be concluded that Lohadosh Nivaraka Yoga is good complementary medication in Thalassaemia.